Proses Berpikir dalam Memecahkan Masalah Trigonometri Ditinjau dari Gaya Kognitif Reflektif dan Impulsif Siswa - Muhammad Ade Syam Agung; Suradi; Ilham Minggi (Issues in Mathematics Education (IMED), 2023)
This research aims to describe students' thinking processes in solving trigonometry problems in terms of reflective and impulsive cognitive styles. It is a descriptive study with a quantitative and qualitative approach. The subjects in this research were four students from the 11th grade of a high school, two students in each group representing the reflective and impulsive cognitive styles based on their results in the trigonometry problem-solving test. Data were collected through tests and interviews. The instruments used for data collection included trigonometry problem-solving tests, MFFT cognitive style tests, and interview guidelines. The results of this research indicate that: (1) Students with a reflective cognitive style and high scores in the trigonometry problem-solving test (SRT)tend to undergo an assimilation process, reaching equilibrium at each stage of problem-solving. (2) Students with an impulsive cognitive style and high scores in the trigonometry problem-solving test (SIT) also experience an assimilation process, reaching equilibrium, but undergo accommodation during the stage of planning problem-solving strategies. (3) Students with both reflective and impulsive cognitive styles and low scores in the trigonometry problem-solving test (SRR and SIR) tend to be in a state of disequilibrium, unable to integrate the existing schemes in their minds with their knowledge.